Pengembangan Bahan Ajar Bahasa Indonesia melalui Eksplorasi Sastra Peranakan Tionghoa di Jenjang Sma - Edith Wenny Puspitasari; Antonius Totok Priyadi; Sesilia Seli (Jurnal Syntax Admiration, 2025)
This research aims to develop innovative and effective teaching materials for learning the structure of short story texts by exploring Chinese Peranakan literature. The teaching materials are developed in the form of an interactive flipbook utilizing multimedia and digital technology. The research method used is research and development, referring to the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The research results indicate that the developed flipbook teaching materials are suitable for use in education, with a feasibility percentage of 98%. Effectiveness testing using a t-test shows a significant difference between the learning outcomes of students using the flipbook teaching materials and those using conventional materials. The 95% confidence interval for the pre-test (52.41 to 62.87) and post-test (81.61 to 87.11) indicates that we can be 95% confident that the true mean lies within this range, confirming a significant improvement. Based on the t-test results, the researcher concludes that the developed teaching materials are effective in enhancing students' understanding. The average improvement from pre-test to post-test shows that students learn better after using the new teaching materials.